Influence of Brand Information on Consumers’ Expectations and Liking of Honey Lemon Healthy Drinks - Fagih, Muhammad; Herdiman, Lobes; Rochman, Taufiq (Jurnal Ilmiah Teknik Industri, 2025)
This study evaluates the impact of brand information on consumer expectations and liking of honey lemon health drinks in Surakarta. The study involved four product samples marketed in Surakarta. Eighty consumers participated in three evaluation conditions: blind test (without brand information), expected test (brand information only), and informed test (complete product information). The evaluation was conducted using a 9-point hedonic scale and Check-all-that-apply (CATA) questions to identify consumer perceptions of the brands. Data analysis included ANOVA and Tukey tests for significant differences, as well as Multiple Factor Analysis (MFA) to compare preferences across conditions. Results showed that brand information significantly affected consumer liking, particularly for well-known brands. These findings provide insights for honey lemon product development, especially in branding strategies to enhance consumer preference.